Home with Mom: The effects of stay-at-home parents on children's long-run educational outcomes - Eric Bettinger; Torbjørn Hægeland; Mari Rege (Statistics Norway, Research Department, 2013)
In 1998 the Norwegian government introduced a program that substantially increased parents' incentives to stay home with children under the age of three. Many eligible children had older siblings, and we investigate how this program affected long-run educational outcomes of the older siblings. Using comprehensive administrative data, we estimate a difference-in-differences model which exploits differences in older siblings' exposures to the program. We find a significant positive treatment effect on older siblings' 10th grade GPA, and this effect seems to be largely driven by mother's reduced labor force participation and not by changes in family income or father's labor force participation.
Keywords: J13; J22; J24; I21; 330; Chas-for-care; Parental time; School performance